The effect of Ginkgo biloba and Nifedipine on DNA breaks in circulating leukocytes of glaucoma patients. (June 2015) - Fang, Lei; Neutzner, Albert; Turtschi, Stephanie; Flammer, Josef; Mozaffarieh, Maneli
<x xml:space="preserve">Abstract</x> Purpose: Oxidative stress plays an important role in the pathogenesis of glaucomatous optic neuropathy. One indirect measure of oxidative stress is the quantification of DNA breaks by comet assay. This study aims to quantify single-stranded DNA (ss-DNA) breaks in circulating leukocytes of glaucoma patients treated with Ginkgo biloba and Nifedipine and compare results with an untreated group. Design: Retrospective clinical study. Participants: Sixty patients with bilateral open-angle glaucoma. Methods: The following groups (n = 20) were retrospectively compared: Primary open-angle glaucoma (POAG) patients without any systemic treatment; POAG patients treated with 5 mg of Nifedipine daily; POAG patients treated with 120 mg of Ginkgo biloba daily. The damage to ss-DNA was quantified as tail-moment by comet assay. Main outcome measures: Damage to single-stranded DNA (ss-DNA) quantified as tail moment in three groups of patients. Results: Patients treated with Ginkgo biloba and Nifedipine exerted a significant lower amount of comet tails indicative of DNA damage, in comparison with control leukocytes of untreated patients (p < 0.001). There was a trend in the difference of tail-moment with the group being treated with Ginkgo biloba having a stronger effect in lowering DNA breaks compared with the group treated with Nifedipine (p = 0.052). Conclusions: POAG patients treated with either Ginkgo biloba or Nifedipine have a lower rate of DNA breaks than POAG patients who are not on these systemic treatments.